Dose-finding designs for early-phase cancer clinical trials : a brief guidebook to theory and practice /: a brief guidebook to theory and practice. ([2019]) - Daimon, Takashi; Hirakawa, Akihiro; Matsui, Shigeyuki
No abstract available